Flavour Compounds in Wine - จันทร์ประสาทสุข, อรอง (KKU Science Journal, 2015)
Wine is an alcoholic beverage which obtained from the fermentation of grape berry or juice constituents, principally the sugars, to a wide range of volatile and non-volatile end products by yeasts under anaerobic condition, consequently the alcohol content of final wine is 9-15%v/v. Additionally, the compounds are formed during the fermentation can generate the wine body and flavours which are the unique characteristic of wine. The wine flavours are composed of more than 1000 compounds which originated from (1) raw material: grape berry and varietal aromas (2) fermentation and (3) aging. The grapes contribute to various non-volatile compounds which are organic acids, terpene compounds and tannin. These compounds canbe metabolized within yeast cells to both of various volatile and non-volatile derivatives that play the important role in the aroma and taste of final wine, namely, alcohols, esters, aldehydes and ketones which are substantially responsible for the bouquets and individual characteristics of a wine. After the fermentation, aging is the process to increase the flavour complexity of wine via a slight oxidation of some either primary or secondary products in wine, and the compounds could be extracted into the wine from the wood casks. The understanding of these compounds formation would help determine the main factors influencing on the wine flavours production and control the consistency of wine quality.